Políticas de educação profissional para pessoas com deficiência - Izaura Maria de Andrade da Silva (2011)
The thesis presented here is the result of a research whose objective was to examine the reasons why education for people with disability has been offered by a differentiated system of schooling, especially as regards the training for the work. In the first stage of the research, a mapping of policies for professional education, as well as professional education programs was carried out to which the person with disability has access. For this, school census data from 2005, 2006 and 2007 were used as a source of study. Besides, a study of legislation and official documents relating to the policies of professional and special education and also interviews with coordinators of programs aimed at inclusion of a person with disability was made. Data obtained from this investigation show school inequalities, such as insignificant registration number of a person with disability in professional technical education, reduction of supply by the education systems in the programs of initial training articulated to basic education designed exclusively for this social segment, in the most part, developed in specialized institutions of private- philanthropic character ; the low effectiveness of programs for inclusion in regular professional education network as a whole, even considering the elementary aspects such as adequacy of physical space and availability of rooms with multifunctional resources. The theoretical framework adopted for analyzing the social and educational exclusion, as well as policies for the social inclusion, is based on Gramscis concepts on hegemony, state, culture, role of intellectuals, school organization in capitalist society and the principle of unity in diversity. It is a dialectical principle that dates back to Marx's reflections, emphasizing that the unit (equality) in diversity (difference) is not the same as inequality. Thus, the idea of equality in diversity helps to explain differences which express inequalities and those who mean respect for diversity. The survey results indicate that the processes of precarious, unstable and marginal exclusion or/and inclusion of a person with disability in social and school organization are due to the way of economic, culture and political organization of the Capitalist State, which demarcates social places, not only to the class in which the subject is located, but also because of racial, ethnical differences and physical, sensory and cognitive conditions. In school organization, mechanisms were elaborated that led to exclusion of the person with disability or her insertion into restricted training places. Mechanisms built on the concept difference / disability comprehended as inability and incapacity being regarded as an immutable condition of the people who were so classified. The movement for the inclusion reframed the concept of difference / disability, considering it as a feature of human diversity which demands some specific strategies and resources to ensure the inclusion processes. The recognition and treatment of these specific demands within the framework of universal policies is an essential aspect in the implementation of the rights of a person with disability to access, permanence and success in school.